Robust α-Fe2O3@TiO2 Core–Shell Structures With Tunable Buffer Chambers for High-Performance Lithium Storage - Pian, Chunyuan; Peng, Weichao; Ren, Haoyu; Ma, Chao; Su, Yun; Ti, Ruixia; Chen, Xiuyu; Zhu, Lixia; Liu, Jingjing; Sun, Xinzhi; Wang, Bin; Niu, Bingxuan; et al. (Frontiers in Chemistry, 2022)
α-Fe2O3 has high potential energy storage capacity and can serve as a green and low-cost anode material for lithium-ion batteries. However, α-Fe2O3 suffers from large volume expansion and pulverization. Based on DFT calculations, TiO2 can effectively maintain the integrity of the crystal structure during the discharge/charge process. Well-defined cubic α-Fe2O3 is coated with a TiO2 layer by the hydrothermal method with the assistance of an oxalic acid surface treatment, and then α-Fe2O3@TiO2 with tunable buffer chambers is obtained by altering the hydrochloric acid etching time. With the joint efforts of the buffer chamber and the robust structure of the TiO2 layer, α-Fe2O3@TiO2 alleviates the expansion of α-Fe2O3 during the discharge/charge process. The optimized sample (FT-1h) achieves good cycling performance. The reversible specific capacity remains at 893.7 mA h g-1, and the Coulombic efficiency still reaches up to 98.47% after 100 cycles at a current density of 100 mA g-1. Furthermore, the reversible specific capacity can return to 767.8 mA h g-1 at 100 mA g-1 after cycling at a high current density. Hence, the buffer chamber and robust TiO2 layer can effectively improve the cycling stability and rate performance of α-Fe2O3.